Composition-dependent contact resistivity in an n-type Mg3SbxBi2−x thermoelectric single leg. (October 2022) - Liang, Zhongxin; Deng, Liangzi; Shi, Xin; Song, Shaowei; Xu, Congcong; Chu, Ching-Wu; Ren, Zhifeng
Abstract: In the current thermoelectric research framework, the material used to assemble a module is selected simply based on its transport properties while assuming that thermoelectric junction contact resistivity values are nearly constant for a specific material matrix, which raises concerns regarding incorrect material selection and thus deficient device performance. Here, by analyzing the thermoelectric performance of a series of Mg3.2 Sb x Bi1.99− x Te0.01 -based compounds, as well as their electrical contact resistivity across the Fe/Mg3.2 Sb x Bi1.99− x Te0.01 /Fe interface, we show that the contact resistivity in the n-type Mg3.2 Sb x Bi2− x thermoelectric single leg is composition-dependent and then demonstrate that the high contact resistivity of a junction based on a material with even the highest figure of merit ( zT ) may considerably restrict performance at the device level. To overcome this dilemma, a multi-layered single leg design is proposed and investigated with the goal to reduce contact resistivity and thus maximize the conversion efficiency of thermoelectric devices. Graphical abstract: Image 1 Highlights: The contact resistivity in n-type Mg3.2 Sb x Bi2 −x single leg is composition-dependent. The predicted conversion efficiency will be limited due to high interfacial resistivity. A multi-layered single leg design is investigated to reduce contact resistivity.